ANALISIS PELAKSANAAN DIVERSI TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM (STUDI KANTOR KEPOLISIAN RESORT KOTA BAUBAU) - Agus Salim; Darmawan Wiridin (Bajang Institute, 2026)
Diversion is a process that allows for the transfer of juvenile cases from formal criminal justice channels to non-criminal justice channels. This approach aims to provide alternative solutions that better prioritize the best interests of children, without requiring them to enter the justice system, which tends to be more formal and harsh. Diversion allows for more humane and restorative solutions, focusing on children's rehabilitation and reintegration into society. This study aims to examine the Implementation of Diversion for Children in Conflict with the Law (Study at the Baubau City Police Station). This research is empirical juridical. The research problem approaches used in this study are: the Legal Approach, the Conceptual Approach, and the Case Approach. Descriptive analysis provides an explanation, depiction, and presentation of an event or legal condition as it is based on the research findings. The results of the study indicate that diversion for child abuse crimes can be concluded as the implementation of diversion for child abuse crimes is in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. In this case, investigators must first consider the category of crime committed by the child when implementing diversion, as this category significantly influences the diversion process. This means that diversion can only be granted to children who commit minor crimes. However, diversion cannot be granted to children who commit serious crimes. Furthermore, investigators must also consider the child's age, as this provision is intended to determine the priority for granting diversion.